Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s13011-020-00336-9
|View full text |Cite
|
Sign up to set email alerts
|

Drug Abstinence Self-Efficacy Scale (DASES): psychometric properties of the Farsi version

Abstract: Background Research has demonstrated that therapeutic interventions based on the self-efficacy theory produce positive outcomes for people who exhibit addictive behaviors, such as alcohol and drug use. Several questionnaires based on self-efficacy theory have been developed to evaluate the extent to which intervention programs can modify behavior. The present study describes the psychometric properties of the Farsi version of the Drug Abstinence Self-Efficacy Scale (DASES). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…The results showed that alcohol, tobacco, and tranquilizers were the substances most commonly used during lockdown, but that there was a reduction in their use. This finding is similar to that reported by Manthey et al ( 42 ) for various European countries, except that in their international survey, marijuana was the third most commonly used substance, after alcohol and tobacco. They believe their results could be partially explained by the reduced availability of substances during the early months of lockdown, as well as a change in the settings where they are used.…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that alcohol, tobacco, and tranquilizers were the substances most commonly used during lockdown, but that there was a reduction in their use. This finding is similar to that reported by Manthey et al ( 42 ) for various European countries, except that in their international survey, marijuana was the third most commonly used substance, after alcohol and tobacco. They believe their results could be partially explained by the reduced availability of substances during the early months of lockdown, as well as a change in the settings where they are used.…”
Section: Discussionsupporting
confidence: 91%
“…Two other studies investigated the quality of complementary or alternative medicine consumer health information for low back pain and neck pain, respectively, and reported that many websites did not adequately report the risks or adverse side-effects of treatment options adequately (Ng and Gilotra 2020 ; Ng et al 2021b ). Similar findings have also been reported with respect to commonly used herbal products such as St. John’s wort (Thakor et al 2011 ), kratom (Ng et al 2021c ), and ephedra (Ng et al 2021d ). Another issue of concern includes the fact that across numerous jurisdictions, even where medical cannabis is legalized, physicians report lacking knowledge and information, while acknowledging their need for greater and continuing education, on this topic (Kansagara et al 2020 ; Philpot et al 2019 ; Ziemianski et al 2015 ; Ng et al 2021e ; Zolotov et al 2018 ).…”
Section: Discussionsupporting
confidence: 80%
“…To measure the CVR, the specialists rated each item as 1 = essential, 2 = useful but not essential, or 3 = not essential. Then, according to the Lawshe table, items with a CVR score of 0.62 or greater were determined to be acceptable and were maintained (20,21,22).…”
Section: Content Validitymentioning
confidence: 99%
“…Afterward, the impact score (importance × frequency) was measured to determine the percentage of addicted persons who recognized an item as important or quite important on a 5-point Likert instrument. An item was determined to be suitable if it had an impact score of 1.5 or higher (21,22,23).…”
Section: Face Validitymentioning
confidence: 99%